2021
DOI: 10.1200/jco.2021.39.15_suppl.3005
|View full text |Cite
|
Sign up to set email alerts
|

Initial results from a dose finding study of TNO155, a SHP2 inhibitor, in adults with advanced solid tumors.

Abstract: 3005 Background: SHP2 transduces signals from activated receptor tyrosine kinases to downstream pathways including MAPK. TNO155 is a selective, allosteric, oral inhibitor of SHP2. Methods: CTNO155X2101 (NCT03114319) is an ongoing first-in-human, open-label dose escalation/expansion trial of TNO155 in adults with advanced solid tumors. The primary objective is to characterize the safety and tolerability of TNO155 and identify regimen(s) for future study. Secondary assessments included pharmacokinetics, pharmac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 0 publications
0
25
0
Order By: Relevance
“…SPH2 inhibition increases KRAS-GDP occupancy what it could increase the effect of direct KRAS G12C (OFF) inhibitors. This also has been demonstrated in preclinical studies of adagrasib combined with SHP2 inhibition (58,(66)(67)(68)(69). Based on this, several ongoing clinical studies with both sotorasib and adagrasib are evaluating the combination of Targeting KRAS in Non-Small Cell Lung Cancer a KRAS G12C (OFF) inhibitor and a SHP2 inhibitor (NCT04330664, NCT04699188, NCT04185883).…”
Section: Combination Of a Krasg12c Inhibitor With Shp2 Inhibitorsmentioning
confidence: 78%
See 1 more Smart Citation
“…SPH2 inhibition increases KRAS-GDP occupancy what it could increase the effect of direct KRAS G12C (OFF) inhibitors. This also has been demonstrated in preclinical studies of adagrasib combined with SHP2 inhibition (58,(66)(67)(68)(69). Based on this, several ongoing clinical studies with both sotorasib and adagrasib are evaluating the combination of Targeting KRAS in Non-Small Cell Lung Cancer a KRAS G12C (OFF) inhibitor and a SHP2 inhibitor (NCT04330664, NCT04699188, NCT04185883).…”
Section: Combination Of a Krasg12c Inhibitor With Shp2 Inhibitorsmentioning
confidence: 78%
“…There are several SHP2 inhibitors in development. RMC-4630 has shown clinical activity with a DCR of 67% for all KRAS mutations, and 75% for KRAS G12C mutations (phase I NCT03989115) ( 11 , 58 , 68 , 69 ). TNO155 is a selective, allosteric, oral inhibitor of SHP2 and is being studied in a phase I trial in advanced solid tumors after disease progression following standard therapy (NCT03114319, NCT04330664) ( 68 , 69 ).…”
Section: Kras and Targeted Therapymentioning
confidence: 99%
“…SHP2 inhibitor enhanced the efficacy of α-PD-1 in murine tumor models [252][253][254]. A clinical study exploring SHP2 inhibitor combined with α-PD-1 is still ongoing (NCT04000529), and the final data of this combination study are not yet available [255].…”
Section: α-Pd-1/pd-l1 Plus Other Novel Targeted Therapiesmentioning
confidence: 99%
“…Notably, results of phase 1 first-in-human clinical trial showed that RMC-4630 led to a disease control rate of 71% in KRAS G12C mutated NSCLC patients (n=19), as a single-agent monotherapy ( 124 ). Likewise, TNO-155 is currently being tested in a phase 1 dose escalation/expansion trial (NCT03114319) in adults with advanced solid tumors alone ( 125 ) or in combination with JDQ443 (KRAS G12C inhibitor), in KRAS G12C patients with advanced solid tumors (NCT04699188).…”
Section: Targeting Acquired Resistance To Kras G12c ...mentioning
confidence: 99%